(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2013)
A wide range of studies supports the assumption that levels of socio-spatial polarization, segregation, and exclusion are rising in global cities over the past decades as a direct outcome of certain global processes, such as the deindustrialization process, its associated changes in division of labor, and declined redistributive power of the welfare state. However, that assumption – known as the polarization thesis – is criticized based on several contentions, including the oversimplification of the global/local interplay by overlooking the role of local contingent factors that may modify, intensify, or reverse the expected socio-spatial outcome in individual cities. This study aims to capture the hybrid nature of the socio-spatial outcomes of global cities by proving that the complex process of restructuring of cities is a form of structural and chronological hybridity. Through providing a solid empirical ground for investigating the general applicability of the socio-spatial polarization thesis, as well as evaluating the influence of local contexts of cities on the outcomes of urban change. The research offers a theoretical review of the multifaceted restructuring of global cities. Then, the macro trends of global economy are linked to their micro outcomes (segregation patterns within cities), through understanding the implications of cities’ economic functions on local urban policies and housing markets. Finally, the changes in socioeconomic segregation over the past decades are calculated for a large dataset of 66 global cities. The collective result of the analysis shows the downfalls of the generalized hypothesis. While the discussion of individual cities highlights certain contextual particularities, that are contributing to the production of unique socio-spatial configurations in different global cities.